Tingkat Kepatuhan Penggunaan Obat Antihipertnsi pada Pasien Hipertensi di Puskesman Gunungsari - Sandra Novelia Safitri; Yoga Dwi Saputra; Mahacinta Andanalusia (MES Bogor, 2025)
Hypertension is a disease that occurs and is characterized by an increase in uncontrolled blood pressure. This uncontrolled disease can result in progressive disease that needs to be treated properly and continuously. Hypertension treatment can be done using antihypertensive drugs. One of the determinants of successful therapy is compliance with the use of antihypertensive drugs by patients. This study aims to provide an overview of the compliance of hypertensive patients in consuming antihypertensive drugs at the Outpatient Installation of Gunungsari Health Center. The design of this study was prospective and analyzed using a descriptive method. This study was conducted on hypertensive patients at the Outpatient Installation of Gunungsari Health Center who underwent control and received antihypertensive therapy where samples were taken using a purposive sampling technique. The data obtained will be analyzed based on the compliance category with the MARS-5 questionnaire. Data will be presented with percentages and pie charts using Microsoft Excel. The results showed that the level of compliance in taking medication for hypertensive patients at Gunungsari Health Center showed a moderate level of 71.58%; a high level of compliance of 18.95%; and low compliance of 9.47%. Factors that affect compliance are forgetfulness, laziness, difficulty remembering medication schedules, and not feeling symptoms of illness. Intensive patient and family education, implementation of reminder strategies, medical personnel monitoring, and innovation in technology-based education methods are required.